2014
DOI: 10.4103/2230-8598.137705
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about childhood bronchial asthma among primary health care personnel in eastern Saudi Arabia

Abstract: Background: Bronchial asthma (BA) is a chronic non-communicable disease affecting children and adults. Despite the availability of written guidelines for diagnosis and management, yet still knowledge and application were inadequate. The aim of this study was to assess asthma knowledge of primary health care centers (PHCCs) personnel in Dammam city, eastern Saudi Arabia. Materials and Methods: This was a cross-sectional study conducted in 22 PHCCs. The sample consisted of 194 personnel (50 physicians and 144 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…in Dammam, Saudi Arabia, reported that about half of primary care personnel showed poor knowledge regarding BA. [ 8 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…in Dammam, Saudi Arabia, reported that about half of primary care personnel showed poor knowledge regarding BA. [ 8 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Taha et al ., it was reported that most PHC personnel in PHCCs in Dammam City, KSA (78.4%) did not receive any training about BA. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations